2000
DOI: 10.1016/s0002-9440(10)64619-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus DNA in Different Histological Subtypes of Cervical Adenocarcinoma

Abstract: The prevalence of human papilloma virus (HPV) DNA in different histological subtypes of cervical adenocarcinoma and related tumors was examined using formalin-fixed, paraffin-embedded tissue samples from 105 primary cervical adenocarcinomas and adenosquamous carcinomas. Broad-spectrum HPV DNA amplification and genotyping was performed with the SPF10 primer set and line probe assay (LiPA), respectively. HPV DNA was detected in 82 of 90 (91%) mucinous adenocarcinomas, encompassing endocervical, intestinal, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
230
3
6

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(258 citation statements)
references
References 45 publications
19
230
3
6
Order By: Relevance
“…5,6 However, the recent more sensitive techniques have made it possible to identify the higher rate of HPV infection in adenocarcinoma with a frequency of 85% or more. [19][20][21] In this study, we used a recently developed HPV DNA Chip for the detection of HPV DNA in 82 of 135 cases. This method is based on the polymerase chain reaction with an advantage to detect single and multiple infection of 22 HPV genotypes at once and has reported to be a very sensitive method comparable with Hybrid Capture II assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 However, the recent more sensitive techniques have made it possible to identify the higher rate of HPV infection in adenocarcinoma with a frequency of 85% or more. [19][20][21] In this study, we used a recently developed HPV DNA Chip for the detection of HPV DNA in 82 of 135 cases. This method is based on the polymerase chain reaction with an advantage to detect single and multiple infection of 22 HPV genotypes at once and has reported to be a very sensitive method comparable with Hybrid Capture II assay.…”
Section: Discussionmentioning
confidence: 99%
“…This result was in accordance with the recent reports by other investigators of Western countries that showed the similar prevalence rate between HPV 16 and HPV 18 in cervical adenocarcinoma. 6,20,23 Accordingly, it is very clear that HPV 18 has a stronger association with cervical adenocarcinoma than with cervical squamous cell carcinoma, where the frequency of HPV 18 (11.4-13.7%) was much less common than that of the cervical adenocarcinoma. Bearing in mind that HPV 18-related cervical carcinomas were associated with poor prognostic factors or poor survival, 24,25 the high frequency of HPV 18 in cervical adenocarcinoma may be implicated in the poorer 5-year survivals of cervical adenocarcinoma compared to squamous cell carcinoma with the same stages as reported by several investigators.…”
Section: Discussionmentioning
confidence: 99%
“…Since more than 92% of the adenocarcinomas and its precursors contain hrHPV (Pirog et al, 2000;Pilch et al, 2001), adding hrHPV testing to conventional cytological screening might improve the present screening programme in detecting adenocarcinoma and its precursor lesions. This should be a focus of further research concerning the functioning of the screening programme for cervical cancer.…”
Section: Incidence and Survival Of Cervical Cancer S Bulk Et Almentioning
confidence: 99%
“…This situation resembles the role played by HPV in the carcinogenesis of uterine cervix where HPV is found not only in squamous cell carcinoma [30], but also in adenocarcinomas [31], and neuroendocrine carcinomas [32,33].…”
Section: Discussionmentioning
confidence: 56%